Comparative Evaluation of Radiochemical and Biological Properties of 131I- and [99mTc]Tc(CO)3-Labeled RGD Analogues Planned to Interact with the αvβ3 Integrin Expressed in Glioblastoma - Danielle V. Sobral; Leonardo L. Fuscaldi; Ana Claudia R. Durante; Fernanda F. Mendonça; Larissa R. de Oliveira; Ana Cláudia C. Miranda; Jorge Mejia; Wagner R. Montor; Marycel F. de Barboza; Luciana Malavolta (MDPI AG, 2022)
Radiolabeled peptides with high specificity for overexpressed receptors in tumor cells hold great promise for diagnostic and therapeutic applications. In this work, we aimed at comparing the radiolabeling efficiency and biological properties of two different RGD analogs: GRGDYV and GRGDHV, labeled with iodine-131 (131I) and technetium-99m-tricarbonyl complex [99mTc][Tc(CO)3]+. Additionally, we evaluated their interaction with the αvβ3 integrin molecule, overexpressed in a wide variety of tumors, including glioblastoma. Both peptides were chemically synthesized, purified and radiolabeled with 131I and [99mTc][Tc(CO)3]+ using the chloramine-T and tricarbonyl methodologies, respectively. The stability, binding to serum proteins and partition coefficient were evaluated for both radioconjugates. In addition, the binding and internalization of radiopeptides to rat C6 glioblastoma cells and rat brain homogenates from normal animals and a glioblastoma-induced model were assessed. Finally, ex vivo biodistribution studies were carried out. Radiochemical yields between 95-98% were reached for both peptides under optimized radiolabeling conditions. Both peptides were stable for up to 24 h in saline solution and in human serum. In addition, the radiopeptides have hydrophilic characteristics and a percentage of binding to serum proteins around 35% and 50% for the [131I]I-GRGDYV and [99mTc]Tc(CO)3-GRGDHV fragments, respectively. Radiopeptides showed the capacity of binding and internalization both in cell culture (C6) and rat brain homogenates. Biodistribution studies corroborated the results obtained with brain homogenates and confirmed the different binding characteristics due to the exchange of radionuclides and the presence of the tricarbonyl complex. Thereby, the results showed that both radiopeptides might be considered for future clinical applications.